Assessment of fresh groundwater vulnerability to contamination caused by production operations in oil and gas fields of Nizhnevartovsk Region (Western Siberia); IOP Conference Series: Earth and Environmental Science; Vol. 43 : Problems of Geology and Subsurface Development - Bespalova Yu. V.; Matusevich V. M.; Popov V. K. Viktor Konstantinovich; Kuzevanov K. I. Konstantin Ivanovich (Hydrogeochemistry and Hydrogeoecology, 2016)
Title screen